DIFFERENT EXERCISE MODALITIES DURING PREGNANCY AND THEIR IMPACT ON MATERNAL AND FETAL HEART RATE VARIABILITY - Bogiel, Zofia; Machała, Antonina; Domański, Andrzej; Dziekońska, Małgorzata; Kowalczyk, Klaudia; Wójcik, Martyna; Wydrych, Andrzej (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Heart rate variability (HRV), reflecting autonomic nervous system activity, emerges as a valuable, non-invasive marker for monitoring maternal and fetal health. It correlates with psychological resilience, inflammatory balance and overall cardiovascular fitness. Although physical activity in pregnancy is widely recommended for its broad health benefits, studies describing its effects on HRV remain limited.Methods: We conducted a comprehensive literature search on Pubmed and Medline databases, with 20 articles selected as relevant to the subject of the study. We included studies where HRV was measured in healthy women in singleton pregnancy who performed various exercise modalities. We excluded the studies where pregnant women took medication which directly affected the cardiovascular system.Research objective: This review aims to synthesize current findings on how different types, intensity and frequency of exercise impact HRV in pregnant women and their fetuses.Key findings: Existing studies demonstrate that low-intensity activities, such as yoga, effectively improve maternal HRV by enhancing parasympathetic tone. Aerobic and Moderate-to-Vigorous Physical Activity (MVPA) also contributes positively when practiced consistently. Research additionally suggests that regular maternal exercise positively influences fetal HRV, indicating better autonomic development and emotional regulation extending into infancy.Conclusions: In conclusion, structured physical activity during pregnancy has the potential to optimize autonomic control in both mothers and their offspring. HRV monitoring may serve as a useful tool for individualizing exercise prescriptions, enhancing maternal-fetal outcomes and help shape future public health guidelines. Further research is needed to clarify optimal exercise protocols in pregnant populations.